Analisis Determinasi Faktor yang Memengaruhi Pendapatan Petani di Agrowisata Kebun Belimbing Desa Ngringinrejo - Yusdiantara, Yusdiantara; Ningsih, Fina Sulistiya; Darsan, Darsan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The starfruit orchard agrotourism in Ngringinrejo Village has great potential in the agricultural sector, which can change the local area's income and environmental sustainability. Farmers in the agrotourism sell both outside and within the agrotourism. This research aims to identify the factors that influence the income of farmers in the starfruit orchard agrotourism of Ngringinrejo village. The location of this research is in Nringinrejo Village, Kalitidu District, Bojonegoro Regency. The sampling was conducted using simple random sampling, resulting in a total of 52 respondents. The data in the study uses both primary and secondary data. The analysis method uses multiple regression with the variables used in this study being X1 farmer's age, X2 number of members, X3 last education, X4 farming experience, X5 land area, X6 number of trees, X7 production costs, X8 production quantity, and X9 selling price. The results of this study indicate that from the regression results of 99%, the variable of production quantity has a significant impact on income.  The factors that have a significant influence are production costs, production volume, and selling price. Meanwhile, other factors such as age, number of family members, farming experience, land area, and number of trees do not have a significant impact on income. Based on this, cost efficiency strategies, optimization of production volume, and pricing become the main focus in increasing revenue.